1994
DOI: 10.1111/j.1365-2958.1994.tb00501.x
|View full text |Cite
|
Sign up to set email alerts
|

Positive selection for resistance to 2‐deoxyglucose gives rise, in Streptococcus salivarius, to seven classes of pleiotropic mutants, including ptsH and ptsl missense mutants

Abstract: We have used the toxic non-metabolizable glucose/mannose analogue 2-deoxyglucose to isolate a comprehensive collection of mutants of the phosphoenolpyruvate:sugar phosphotransferase system from Streptococcus salivarius. To increase the range of possible mutations, we isolated spontaneous mutants on different media containing 2-deoxyglucose and various metabolizable sugars, either lactose, melibiose, galactose or fructose. We found that the frequency at which 2-deoxyglucose-resistant mutants were isolated varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 44 publications
1
26
0
Order By: Relevance
“…In a previous study, we reported that several types of PTS-negative mutants could be isolated by plating S. salivarius on a medium containing 2DG and a metabolizable sugar (11). We observed that the frequency at which mutants could be isolated was highest with the combination 2DG and galactose and that selection on galactose seemed to favor the isolation of ptsH mutants.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…In a previous study, we reported that several types of PTS-negative mutants could be isolated by plating S. salivarius on a medium containing 2DG and a metabolizable sugar (11). We observed that the frequency at which mutants could be isolated was highest with the combination 2DG and galactose and that selection on galactose seemed to favor the isolation of ptsH mutants.…”
Section: Resultsmentioning
confidence: 95%
“…The nucleotide sequences of the ptsH and ptsI genes were determined as described by Gauthier et al (11). The sequence of the region upstream from the Ϫ35 box of the pts promoter was obtained after amplification of a 398-bp DNA fragment by PCR using two oligonucleotides (5Ј-TATCTTTACAGCTGACTTAG-3Ј and 5Ј-GCTGGACGTGCGTGGAT-3Ј) that annealed with a region of the idh gene located 252 bp upstream from the Ϫ35 region of the pts promoter and with a region in the ptsH gene.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Strain G22.4 is an isogenic spontaneous mutant isolated from S. salivarius that has a missense mutation in the ptsH gene, resulting in the substitution of the isoleucine at position 47 (Ile-47) in HPr by a threonine (Thr) (Gauthier et al, 1994). Cells were grown at 37ЊC in a medium containing 10 g of tryptone and 5 g of yeast extract (Difco Laboratories), 2.5 g of NaCl and 2.5 g of disodium phosphate per litre.…”
Section: Methodsmentioning
confidence: 99%
“…Mutant G22.4 is a spontaneous 2-deoxyglucose (2-DG)-resistant mutant isolated from S. salivarius 25975 that has a missense mutation in the HPr protein resulting in the replacement of the isoleucine at position 47 (Ile-47) by a threonine (I47 →T) (Gauthier et al, 1994). Ile-47 is adjacent to the serine residue (Ser-46) that is phosphorylated by the ATP-dependent HPr kinase in Gram-positive bacteria and is also believed to be involved in the interaction of HPr with EI of the PTS (Herzberg et al, 1992).…”
Section: Phosphorylation Of Pts Proteins In Mutant G224mentioning
confidence: 99%